Agile Laravel-Based e-HMS for Secure Appointment Booking and Role-Based Clinical Workflow Management - Mardiyya Lawal Bagiwa; Barira Hamisu; Raji Abdullahi Egigogo; Muhammad Yahaya Gana (Yayasan Cendekiawan Digital Indonesia, 2025)
The rapid expansion of digital health platforms increased access to healthcare services, yet many electronic healthcare management systems remained fragmented, poorly structured, and weakly integrated, limiting reliable appointment coordination, data consistency, and secure information access. This research developed and implemented a web-based electronic healthcare management system (e-HMS) using the Laravel framework to consolidate appointment scheduling, treatment documentation, and role-based interaction among patients, healthcare providers, and administrators. The system was developed using an agile software development approach, with iterative requirements engineering, architectural modeling, and modular implementation, following the Model–View–Controller paradigm. Empirical validation was conducted using requirement-driven unit testing across three functional modules, comprising 29 test cases derived from administrative, provider, and patient workflows. Functional conformity was assessed via pass fail analysis of authentication, appointment lifecycle management, treatment recording, and communication features, with all test cases passing. The resulting system demonstrated that workflow-oriented, role-based architectures can improve structural coherence and operational reliability in web-based healthcare platforms. This work contributed an implementable reference model for scalable and secure e-health system design, applicable to healthcare environments seeking interoperable, extensible digital solutions beyond local institutional contexts.